Ambulance Dispatches From Unaffected Areas After the Great East Japan Earthquake: Impact on Emergency Care in the Unaffected Areas. (28th July 2015) - Hagihara, Akihito; Onozuka, Daisuke; Nagata, Takashi; Abe, Takeru; Hasegawa, Manabu; Nabeshima, Yoshihiro
Abstract: Objective: Although dispatching ambulance crews from unaffected areas to a disaster zone is inevitable when a major disaster occurs, the effect on emergency care in the unaffected areas has not been studied. We evaluated whether dispatching ambulance crews from unaffected prefectures to those damaged by the Great East Japan Earthquake was associated with reduced resuscitation outcomes in out-of-hospital cardiac arrest (OHCA) cases in the unaffected areas. Methods: We used the Box-Jenkins transfer function model to assess the relationship between ambulance crew dispatches and return of spontaneous circulation (ROSC) before hospital arrival or 1-month survival after the cardiac event. Results: In a model whose output was the rate of ROSC before hospital arrival, dispatching 1000 ambulance crews was associated with a 0.474% decrease in the rate of ROSC after the dispatch in the prefectures ( p= 0.023). In a model whose output was the rate of 1-month survival, dispatching 1000 ambulance crews was associated with a 0.502% decrease in the rate of 1-month survival after the dispatch in the prefectures ( p= 0.011). Conclusions: The dispatch of ambulances from unaffected prefectures to earthquake-stricken areas was associated with a subsequent decrease in the ROSC and 1-month survival rates in OHCA cases in the unaffected prefectures. ( Disaster Med Public Health Preparedness . 2015;9:609–613)